Belief Systems, Religion, and Behavioral Economics - Minton, Elizabeth A (Business Expert Press, 2014)
Ebook from IG Library ; Religion is a topic that businesses often ignore, in spite of 70% of the world being religious. Whether the silence results from the taboo nature of the topic or the thought that religion is a separate domain from consumption and business, the scant attention cannot be denied. Many do not realize or simply resist the idea that religion is a key contributor to a consumer's core values, which then contribute to consumption decisions, voting practices, reaction to pro-social messages and public policy, as well as donating behavior. The field of behavioral economics discusses how various social and cognitive factors influence economic decision making, which encompasses consumer decision making in business and public policy. This field needs to incorporate religion as an influencer to economic decision making. To be able to manage a business effectively, or carry out public policy decisions, the influence of believe systems and religion must be taken into account. Thus, this book provides one of the first comprehensive investigations into the relation between religion and behavioral economics. It is relevant to current managers, anyone involved in the marketing, MBA students, and also upper-division undergraduate students. Each of these groups will benefit from a clear understanding of religious groups and how religion influences consumer decision making.